Gastrointestinal stromal tumor (GIST) with glandular component. A report of an unusual tumor resembling adenosarcoma - Zámecník, M; Sosna, B; Chlumská, A (Ceskoslovenska patologie, 2005)
A case of gastrointestinal stromal tumor (GIST) with an unusual glandular component is reported. The tumor was found in the gastric fundus of a 93-year-old woman. Histologically, the lesion showed a biphasic adenosarcoma-like structure. Typical low-grade spindle cell patterns of GIST were intermingled with numerous and partly cystic glands. The glandular epithelium had pyloric/foveolar-like appearance, with foci of intestinal metaplasia and low-grade dysplasia. The stromal component was immunoreactive for CD117 (c-kit) and CD34, and negative for myoid and neuroid markers. The ultrastructural examination found nondescript and undifferentiated spindle cells. The gastric mucosa and submucosa near the tumor contained a small area with features of gastritis cystica profunda, with glands similar to those present inside the tumor. Therefore, a collision of GIST and gastritis cystica profunda is suggested in the histogenesis of the lesion.
Keywords: Aged, 80 and over; adenosarkom; nádory žaludku; Female; gastrointestinální stromální tumory; senioři nad 80 let; Adenosarcoma; Humans; ženské pohlaví; Gastrointestinal Stromal Tumors; lidé; Stomach Neoplasms